Application of Occupational Therapy Drawing and Dhikr as A Nursing Intervention to Overcome Auditory Hallucinations: Case Report - Agustin, Herlina; Ramadhan, Indah; Mulyaningrat, Wahyudi (Jurnal Ilmiah Ners Indonesia, 2026)
Schizophrenia is a severe mental disorder characterized by hallucinations, particularly auditory hallucinations. Pharmacological therapy is often not optimal, so nonpharmacological interventions are needed. This study emphasizes the novelty of combining drawing therapy and dhikr therapy. Drawing therapy helps patients express emotions and shift attention away from hallucinations, while dhikr provides spiritual calmness. The purpose of this case report is to determine the effect of occupational therapy, drawing and dhikr in overcoming patients with auditory hallucinations. This descriptive case report involved two schizophrenia patients with auditory hallucinations at Dr. Arif Zainudin Mental Hospital, Central Java. The intervention was conducted over three consecutive days (40–50 minutes per session). Evaluation was carried out using symptom observation and the Auditory Hallucination Rating Scale (AHRS). The results showed a decrease in the Auditory Hallucination Rating Scale in both patients, with client 1 experiencing a reduction from 13 to 6, while client 2 decreased from 29 to 22. Observations also indicated a reduction in the frequency and intensity of auditory hallucinations, as well as an increase in calmness and focus during therapy.  The application of occupational drawing therapy and dhikr is effective in reducing the symptoms of auditory hallucinations. In nursing practice, structured motor activities such as drawing are more effective in interrupting acute hallucinations, while dhikr serves as a supportive therapy for emotional regulation.